An improved synthesis technique for optical circuits using MIG and XMG. (February 2022) - Das, Rakesh; Bandyopadhyay, Chandan; Rahaman, Hafizur
Abstract: The progress of fabrication technology in the photonics industry has achieved a significant milestone due to the practicability of performing functional computations on-chips using ultra-high-speed optical devices and low-power interconnects. These rapid advancements in the optical industry have generated a huge interest before the research community towards developing algorithms for efficient synthesis of optical circuits, and in the last few years several articles have come out in this field. Use of graph data structures like BDD, AIG is investigated as intermediate representations (IR) to perform scalable synthesis for logic functions. However, optimizing the generated circuits and developing efficient synthesis schemes remain a high priority in this highly growing field. Motivated by the rapid progress made in optical circuit design, in this work, we introduce an improved synthesis scheme based on two prominent graph data structures - MIG and XMG, where both the graphs act as IR in designing optical circuit. The synthesis steps are completed in two phases, wherein the first phase, we find the intermediate representation (IR) for the input function and then, we perform the technology mapping from the obtained IR to MZI circuit. This second phase also has two more sub-phases where first we run a template matching algorithm and then a set of optimization rules are executed to improve the cost. In our design, we use three primary optical components – MZI, beam combiner and splitter but as the use of beam splitter in circuits reduces the signal strength, we also have shown the way of transforming a normal circuit to splitter-free design. Our synthesis approach can handle large functions and have shown good results for a wide spectrum of benchmarks. Comparison with related state-of-the-art IR based approaches has registered some good improvements too.